Compression for Great Video and Audio - Waggoner, Ben (Elsevier, 2011)
Learn how to compress video and audio with optimal quality and minimal hassles. Renowned expert Ben Waggoner teaches you to improve the quality of your final content and develop effective workflows. Understand the basic concepts of vision and hearing, apply that knowledge in the context of compression, then move onto practical, applicable information for creating, editing, and compressing the best video and audio, whether you’re delivering for the web, DVD, Blu-ray, phones, or beyond.